Preventing medication errors - Carey, Lawrence, PharmD; Miller, Donna, CCRN.; Springhouse Corporation (Springhouse, PA : Springhouse Corp., 2001)
Tells how to safely administer medications, prevent common medication errors, document medication and report medication errors
Videocassette is available at Koleksi Media Perpustakaan HUKM
Approved for 2.0 contact hours CE credit with completion of post-test
Keywords: Medication Errors -- prevention & control -- nurses' instruction